Update on the role of antiseptics in the management of chronic wounds with critical colonisation and/or biofilm - Alves, Paulo J. (2021)
Biofilms play a major role in delaying chronic wounds from healing. A wound infiltrated with biofilm, or “critically colonised” wound, may become clinically infected if the number of microbes exceeds a critical level. Chronic wound biofilms represent a significant treatment challenge by demonstrating recalcitrance towards antimicrobial agents. However, a “window of opportunity” may exist after wound debridement when biofilms are more susceptible to topical antiseptics. Here, we discuss the role of antiseptics in the management of chronic wounds and biofilm, focusing on povidone-iodine (PVP-I) in comparison with two commonly used antiseptics: polyhexanide (PHMB) and silver. This article is based on the literature reviewed during a focus group meeting on antiseptics in wound care and biofilm management, and on a PubMed search conducted in March 2020. Compared with PHMB and silver, PVP-I has a broader spectrum of antimicrobial activity, potent antibiofilm efficacy, no acquired bacterial resistance or cross-resistance, low cytotoxicity, good tolerability, and an ability to promote wound healing. PVP-I represents a viable therapeutic option in wound care and biofilm management, with the potential to treat biofilm-infiltrated, critically colonised wounds. We propose a practical algorithm to guide the management of chronic, non-healing wounds due to critical colonisation or biofilm, using PVP-I.